Internal membrane fouling by proteins during microfiltration - Lay, Huang Teik (2022)
The current study aimed to understand both external and internal membrane fouling by three proteins with different net charges, namely, negatively charged pepsin and bovine serum albumin (BSA), as well as positively charged lysozyme. Polycarbonate track-etched (PCTE) membranes were used. Per electrostatic attraction, the flux decline was the worst for lysozyme, which is attributed by the fouling model to the greatest pore blockage (α) and pore constriction (β), and by field-emission scanning electron microscope (FESEM) and optical coherence tomography (OCT) to the most extensive external fouling. Between pepsin and BSA, BSA gave worse flux decline despite its more negative net charge. The fouling model indicates that BSA gave greater pore blockage (α) and denser internal cake (Rc/Rm), while the quartz crystal microbalance with dissipation (QCM-D) indicates a rigid cake structure. Notably, despite monotonic flux decline with filtration, the OCT fouling voxel trends show significant fluctuations, which has not been reported before and thus signify the unique behavior of protein foulants in straight-through pores. Specifically, the trends below and above the −4.5 μm layer (i.e., 4.5 μm below the feed-membrane interface) are perfectly opposite, indicating the non-uniform protein deposits slipping downwards in the membrane pores as filtration progressed. The dynamic movements of the protein cakes unveiled here warrant more understanding in future studies.